Dry/Wet Cycles Change the Activity and Population Dynamics of Methanotrophs in Rice Field Soil - Ma, Ke (American Society for Microbiology, 2013)
The methanotrophs in rice field soil are crucial in regulating the emission of methane. Drainage substantially reduces methane emission from rice fields. However, it is poorly understood how drainage affects microbial methane oxidation. Therefore, we analyzed the dynamics of methane oxidation rates, composition (using terminal restriction fragment length polymorphism [T-RFLP]), and abundance (using quantitative PCR [qPCR]) of methanotroph pmoA genes (encoding a subunit of particulate methane monooxygenase) and their transcripts over the season and in response to alternate dry/wet cycles in planted paddy field microcosms. In situ methane oxidation accounted for less than 15% of total methane production but was enhanced by intermittent drainage. The dry/wet alternations resulted in distinct effects on the methanotrophic communities in different soil compartments (bulk soil, rhizosphere soil, surface soil). The methanotrophic communities of the different soil compartments also showed distinct seasonal dynamics. In bulk soil, potential methanotrophic activity and transcription of pmoA were relatively low but were significantly stimulated by drainage. In contrast, however, in the rhizosphere and surface soils, potential methanotrophic activity and pmoA transcription were relatively high but decreased after drainage events and resumed after reflooding. While type II methanotrophs dominated the communities in the bulk soil and rhizosphere soil compartments (and to a lesser extent also in the surface soil), it was the pmoA of type I methanotrophs that was mainly transcribed under flooded conditions. Drainage affected the composition of the methanotrophic community only minimally but strongly affected metabolically active methanotrophs. Our study revealed dramatic dynamics in the abundance, composition, and activity of the various type I and type II methanotrophs on both a seasonal and a spatial scale and showed strong effects of dry/wet alternation cycles, which enhanced the attenuation of methane flux into the atmosphere.